Analisis Dampak Perundungan Verbal terhadap Konsentrasi dan Prestasi Akademik Siswa di Sekolah Dasar - Nissa Putri Yanti; Nola Nofita Sari; Safrizal Safrizal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Verbal bullying is a serious issue in elementary school environments that is often underestimated, despite its significant impact on students’ psychological well-being and academic performance. This study aims to analyze the impact of verbal bullying on students’ learning concentration and academic achievement at Elementary School. The research employed a qualitative approach using a case study design. The participants consisted of six informants selected through snowball sampling, including the principal, teachers, and students. The researcher acted as the main research instrument, supported by interview guidelines, observation sheets, and documentation tools. Data were collected through in-depth interviews, observations, and document analysis. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through technique and source triangulation. The findings indicate that verbal bullying is the most dominant form of bullying occurring at Elementary School, particularly in the form of mocking physical characteristics and mentioning parents’ names. Verbal bullying directly affects students’ learning concentration, leading to decreased focus during classroom activities, reduced learning motivation, and declining academic achievement. In addition, verbal bullying causes psychological impacts such as fear, discomfort, low self-confidence, and emotional distress among students. The study concludes that verbal bullying not only affects students’ social and psychological aspects but also has direct implications for the learning process and academic performance. Therefore, serious preventive and intervention efforts from schools are necessary to create a safe and supportive learning environment.